Analisis Minat Belajar Lagu Daerah Bagi Peserta Didik Kelas IV SD Negeri Malahayu 03 Kecamatan Banjarharjo - Warnengsih, Muamar; Laelia Nurpratiwiningsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the interest in learning folk songs in fourth grade students of SD Negeri Malahayu 03 Banjarharjo District. Interest in folk songs is important because folk songs are a mirror of national identity. This research uses a qualitative approach. The subjects of this study were fourth grade students at SD Negeri Malahayu 03. The focus of the research was on problems related to the causes of the students' lack of interest in folk songs. Data obtained by using observation, interviews and documentation. Data analysis uses three steps, namely: data reduction, data presentation and drawing conclusions or verification. The validity of the data was obtained through triangulation technique. The data from the results of this study showed that internal and external factors were the cause of the lack of interest of students in folk songs. The internal factors that cause a lack of student interest in folk songs are: a. students are more interested in pop songs and dangdut; b. have no singing talent; c. find it difficult to learn folk songs in terms of poetry and melody. Meanwhile, the external factors that caused it were: a. the teacher did not provide motivation for the introduction of folk songs b. the ineffectiveness of art extracurricular activities, c. the development of modern art; d. lack of motivation from parents in directing students to choose educational songs.